Social Religious Construction in the Tuatunu Indah Village Community in Facing the Covid-19 Pandemic - Tyas Fadhilla salsa; Iskandar Zulkarnain; Aimie Sulaiman (Profesional Muda Cendekia Publishing, 2023)
The policy issued by the government in an effort to break the chain of thespread of the covid-19 virus which is stated in PP Number 21 of 2020concerning Large-Scale Restrictions (PSBB) and the fatwa issued by MUI(Indonesian Ulema Council) regarding fatwa number 14 of 2020concerning the implementation of worship in the situation of the covid-19outbreak has raised pros and cons in society. New social constructionemerges as a form of reaction from the community in responding to socialrealities and social phenomena at this time, one of which is theimplementation of the five daily prayers in the mosque. To reveal thisreality, researchers tried to analyze the behavior of the Tuatunu Indahurban community in dealing with the pandemic and explain how theprocess of forming social construction related to the co-19 pandemic. Thisresearch was conducted using a qualitative research method with aphenomenological approach. Researchers collected data using observation,interview and documentation techniques. The data analysis technique wascarried out by using data management components such as datareduction, data display and conclusion drawing. The theory used is thetheory of social construction by Peter L Berger, this theory was chosen toexplain the process of forming social construction of the Tuatunu IndahVillage community in dealing with the co-19 pandemic. The resultsshowed that community behavior in dealing with the covid-19 pandemicdepends on the role of actors, especially when conveying messages throughsurahs in the Koran and hadiths on how to deal with the covid-19pandemic. In addition, the results also show that regulations and policiesin dealing with the covid-19 pandemic have received a negative responsefrom the Tuatunu Indah community